PENGGUNAAN TANAH LIAT SEBAGAI BARAN KONSTRUKSI LAPISAN AUS JALAN HUTAN Using clay. soil for wearing course material of forest roads - S Sutopo (Jurnal Penelitian Hasil Hutan, 1990)
Oil type  of forest areaB in Indonesia is dominated by  c"lay.  This soil is poor. when used a  forest road construction material but its engineering properties can be improved by certain treatments.C"lay soils can be used aB binding materialaof wearing course construction. An investigation wa. carried out, using the mi:cture of soil, lime and crushed rock with the following results: 1. Lime haB a highly significant influence on the binding strength of materaUfor wearing course of forest road& It proportion is 1~  on weight bas~.                                    2. According to laboratory test, the use of cruthed rock has a highly significant influence on wearingcource  tre"lth.Percentagesof separated materials at 0%. 2590. 50% and 75% cmshed rock mixture are 1,0%. 2,5%, 26,B'foand 66.5%reapectively.3. An effective crushed rock percentase for clay 11oil wearingcourse construction is 25%. Among the material mixtUre(soU, lime and cmshed rock) have significant interaction.